Optimizing Electricity Consumption on Construction Site Using a Monitoring System - Krištofič, Štefan; Antošová, Naďa (Vysoké učení technické v Brně,Fakulta stavební, 2024)
This research focuses on the optimization of electricity consumption on a construction site through the implementation of a monitoring system. The construction industry is known for its high energy demands and therefore, efficient electricity management is a key element for the economic sustainability of projects and the reduction of environmental impact. In this research, a monitoring system is deployed to collect real electrical energy data at the construction site. This data is then analysed to identify consumption patterns and develop algorithms for the optimal management of electrical loads. As a result of this work, electricity costs will be reduced and the negative impact on the environment will be reduced.
Keywords: Consumption optimization; construction site; electricity consumption